A Two Element Plasma Antenna Array - Sadeghikia, F.; Hodjat-Kashani, F. (Engineering, Technology & Applied Science Research, 2013)
This theoretical study presents the characteristics of plasma monopole antennas in the VHF/UHF range using finite difference time domain (FDTD) simulation. Results show that more broadband characteristics can be obtained by increasing the diameter of the plasma tube and that the minor lobes diminish in intensity as diameter increases. Furthermore, the nulls are replaced by low level radiation. Since the collision frequency, which is a function of gas pressure, represents the loss mechanism of plasma, decreasing its value increases the gain and radar cross section (RCS) of the antenna. Theoretical modeling shows that at higher plasma frequencies with respect to the signal frequency, the gain and radar cross section of the plasma antenna are high enough and that the impedance curves are altered as the plasma frequency varies. Using these preliminary studies, mutual impedance and gain of a broadside array of two parallel side-by-side plasma elements is presented.